Evolutionary micro-dynamics and changes in the economic structure - André Lorentz; Maria Savona (Max Planck Institute of Economics, 2007)
The paper aims to account for the empirical stylised facts related to changes in sectoral structures that have led to the growth of services in most advanced countries over recent decades. A growth model with evolutionary micro-founded structural change is developed, which formalises the role of technical change and changes in intermediate demand as they affect the evolution of the sectoral composition of the economy and macro-economic growth. Firstly, we provide a micro-foundation for the Kaldorian Cumulative Causation mechanism. Secondly, we account for (demand-related) macro-constraints affecting the micro-behaviour of firms in the decision to adopt technology. We also formalise the mechanisms transmitting the effects of micro-behaviour on aggregate growth, via changes in the intermediate linkages and sectoral composition of the economy. The simulated results are based on the use of the actual data, including Input-Output (I-O) coefficients in the case of Germany. Three scenarios are identified, which account for the effects of a set of key parameters on changes in the structure of the economy.
Keywords: E11; L16; O14; O33; O41; 330; Economic Growth; Structural change; Growth of Services; Evolutionary Micro-foundation; Input-Output; Strukturwandel; Drei-Sektoren-Hypothese; Evolutionsökonomik; Mikroökonomische Fundierung; Input-Output; Theorie; Deutschland